Detecção e degradação eletroquímica de dexametasona usando eletrodos de diamante dopado com boro - Alves, Eliezer de Oliveira (Universidade Federal de São Carlos, 2022)
Dexamethasone is a glucocorticoide, first synthesized in 1957, that is currently part of the World Health Organization's List of Essential Medicines. Thus, as na important drug, its potential for environmental contamination has drawn attention in recent years, especially after the increase in its consumption due to its use in the treatment of COVID-19. Thus, the development of simple, fast, and sustainable techniques for the determination and treatment of aqueous matrices containing dexamethasone is a necessity. This work presents electrochemical methods with the desirable characteristics for the determination and degradation of dexamethasone using boron-doped diamonds as electrode material. For the determination, a method was developed using the differential pulse voltammetry technique, using the peak current from the oxidation of dexamethasone on boron-doped diamond with anodic pretreatment as analytical sign. The determinations were performed in a 0.04 mol L–1 H3PO4 medium as the supporting electrolyte, obtaining in the best conditions a linear range of 2.0–40.0 μmol L–1 (R2 = 0.999), with a detection limit of 2.0 μmol L–1 (S/N = 3). As for the electrochemical degradation method, a flow system was used with a filter-press reactor fitted with turbulence promoters. Applying a current density of 20 mA cm–2, the complete removal of dexamethasone (40 mg L–1 in 0.1 mol L–1 Na2SO4) was attained, with a mineralization of 82% in 5 h of treatment.
Electrochemical detection and degradation of dexamethasone using boron-doped diamond electrodes
Keywords: Diamante; Diamond; Electrochemical; Eletroquímica; Degradação; Degradation; Detecção; Detection; Dexametasona; Dexamethasone; Eletrodo; Electrode; Voltametria; Voltammetry; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA